Implications of the Pandemic Wave on the Entrepreneurial Initiative in Romania - Claudia-Florina BOTAR (CECCAR Business Review, 2023)

(untitled)
Measuring the implications of the shock wave propagated following the outbreak of the coronavirus pandemic is becoming an exhausting process. The negative impact on the business environment during the sanitary crisis certifies the imbalance occurred within the entrepreneurial initiative, based on the uncertainty felt in the financial area and equally in the emotional one, emphasizing the vulnerability, incertitude and instability of those who intend to develop and apply a business plan. This article highlights the degradation of the entrepreneurial activity during the pandemic, based on the statistical analysis regarding the action of setting up an entity and not only that, emphasizing the influence promoting factors of the behaviour related to the adoption of the entrepreneur status, given the circumstances created by the sanitary crisis, with great effect on the economic world. Likewise, the issues regarding the suspension of a company’s activity provides indices with regard to the seriousness of the situation induced by the COVID-19 pandemic, being analysed during the work. The adjustment and relaunching of the post-pandemic economic activity remains a desideratum of the economic world, even after a significant period from the disappearance of the pandemic wave.